Behavioral Return Interventions - How Behavioral Science Helps Prevent Returns in E-Commerce - Thilo Pfrang; Philipp Spreer (Marketing Review St.Gallen, 2022)
From the customer, company, and sustainability perspectives, it is agreed that e-commerce returns should be avoided. However, practical approaches to preventing returns are lacking. A large-scale experiment in four European countries now shows that behavioral design interventions ("nudging") can prevent millions of returns.
Keywords: 650